Pengaruh Price Discount, Bonus Packc Dan Store Atmosphere Terhadap Impulse Buying (Studi kasus Toko UD Pokok Berkah) - Niko Aditya; M. Ridwan Basalamah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe shift in consumer behavior in Indonesia is the main influence of increasing consumer demand. Consumer behavior tends to be impulsive, and this is especially true for consumers at toko UD pokok berkah Malang. This study aims to examine the relationship between impulse buying, price discounts, bonus packs, and store atmosphere. The sample consists of 100 respondents where they are selected by purposive sampling. Characteristics of respondents, for example, they live in the city of Malang, they have shopped at toko UD pokok berkah, respondents aged 15-45 years. Analysis using analisis regresi linear berganda on SPSS20. It was found that the discount price, bonus pack, and store atmosphere had a simultaneous effect on impulse buying, while for a partial effect only bonus packs had no effect on impulse buying. Keyword: price discount, bomus pack, store atmosphere, impulse buying